Transtemporal Ultrasound (US) Assessment of Third Ventricle Diameter (TVD): Comparison of US and MRI TVD in Pediatric Patients - Kerscher, Susanne R.; Schweizer, Louise L.; Nägele, Thomas; Bevot, Andrea; Alber, Michael; Schuhmann, Martin U. (Neuropediatrics, 2020)
Introduction In a retrospective magnetic resonance imaging (MRI)-based study, we showed that changes of the third ventricle diameter (TVD) are a reliable mirror of changes of the entire ventricular system. The third ventricle is easily accessible in more than 90% of children and adults using ultrasound (US) via the transtemporal bone-window; thus it can be assessed quickly and free of radiation. In order to use transtemporal US determination of TVD instead of MRI/CT in clinical practice, it is important to know if there is a correlation and bias between both methods, which is addressed in this study.Materials and Method This prospective study investigates 122 children (newborn–18 years). Diagnoses encompassed hydrocephalus (50%), tumors (14.8%), and other intracranial pathologies (35.2%). US-based TVD was measured via the transtemporal bone-window using a phased array 1 to 4MHz transducer. Results were compared with TVD measured on simultaneously acquired axial T1-weighted axial MRI or computed tomography (CT) scans.Results Overall mean values for TVD were 6.56 ± 5.84 and 6.47 ± 5.64 mm for US and MRI, respectively. There was an outstanding correlation between TVD measured by MRI and US (r = 0.991, p < 0.01). Bland–Altman analysis showed a mean bias of 0.096 mm with limits of agreement of –0.99 and 1.18 mm.Conclusion US- and MRI-based TVD measurements correlate excellently and measure almost identical TVD values. US-based TVD is in mean ∼0.096 mm larger than MRI-based TVD due to a more angulated measurement plane. US is equal to the gold-standard MRI, a fact, opening new avenues for US-based TVD as a first-line assessment tool of ventricular width.
Keywords: ventricular system; third ventricle diameter; US- and MRI-based TVD; hydrocephalus; TVD